Process for the preparation of porous mineral supports based on phosphogypsum from solid waste materials of large volume

CN122586424APending Publication Date: 2026-08-18XIAN YUNZHIJING ECOLOGICAL TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610925764.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-25
Publication Date
2026-08-18

AI Technical Summary

Technical Problem

然而,现有技术多针对某一种固废进行单独处理,缺乏将磷石膏与煤矸石、矿渣、赤泥等多种大宗固废进行协同利用的系统性方案

Benefits of technology

[0026] (1) This invention uses phosphogypsum as the main raw material and synergistically utilizes various bulk solid wastes such as coal gangue, S95 slag powder, and red mud to leverage the complementary advantages of different solid wastes in terms of chemical composition and physical properties. Phosphogypsum provides a calcium source, while coal gangue, slag powder, and red mud provide active silicon and aluminum components, generating CSH and CASH gels under alkaline activation conditions to form a stable gel skeleton. This achieves large-scale disposal of various solid wastes, avoiding the problems of low utilization rate and poor performance of single solid wastes, and improving the comprehensive utilization level of solid waste resources.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122586424A_ABST
    Figure CN122586424A_ABST
Patent Text Reader

Abstract

This invention discloses a method for preparing a phosphogypsum-based porous mineral carrier based on bulk solid waste materials, belonging to the field of solid waste resource utilization. The method uses phosphogypsum as the main raw material and coal gangue, S95 slag powder, red mud, and other auxiliary solid wastes as alkali-activated precursors. After drying, crushing, and screening, the materials are mixed in proportion and then subjected to a combined primary water washing and multi-stage alkali washing to remove impurities. Calcium stearate is added as a foam stabilizer, and a low-dosage liquid sodium silicate dilution and hydrogen peroxide dilution are atomized and sprayed into a disc granulator for wet granulation and chemical gasification to create pores. After ambient temperature curing, drying, and screening, granular porous mineral carriers are obtained. This invention, through the synergistic effect of low-dosage silicate cementation, mineral particle embedding, and hydrogen peroxide gasification to create pores, obtains framework-type mineral carrier particles that possess skeletal stability, air and water permeability, and efficient solidification ability for harmful components. These particles can be used in soil conditioners, soil amendments, and as framework materials for microbial and nutrient loading carriers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of solid waste treatment technology, specifically relating to a method for preparing phosphogypsum-based porous mineral carriers based on bulk solid waste materials. Background Technology

[0002] Phosphogypsum is a major industrial byproduct of wet-process phosphoric acid production, generating approximately 4-5 tons of phosphogypsum for every ton of phosphoric acid produced. Currently, my country's annual phosphogypsum production exceeds 80 million tons, with accumulated stockpiles exceeding hundreds of millions of tons. The main component of phosphogypsum is calcium sulfate dihydrate, but it also contains harmful components such as free acid, soluble phosphorus, soluble fluorine, heavy metals (e.g., arsenic, cadmium, lead, chromium, mercury), and naturally occurring radioactive nuclides. Its pH value is typically between 2 and 4, making it strongly acidic. The long-term open-air stockpiling or damming of large quantities of phosphogypsum not only occupies valuable land resources but also poses potential risks to surrounding soil, surface water, and groundwater environments through migration via acidic leachate.

[0003] Currently, the main ways to utilize phosphogypsum include as a cement retarder, in gypsum building materials (such as paper-faced gypsum board and gypsum blocks), and as roadbed materials. However, in practical applications, impurities such as soluble phosphorus, fluorine, and heavy metals in phosphogypsum can significantly affect the performance and environmental safety of building materials. For example, soluble phosphorus can delay cement setting time, and soluble fluorine can corrode production equipment. When used as a soil conditioner, if harmful components are not effectively solidified, long-term application may lead to the risk of heavy metal accumulation in the soil. Therefore, harmless pretreatment of phosphogypsum is a necessary prerequisite for its safe resource utilization.

[0004] Existing technologies for the pretreatment of phosphogypsum mainly employ single or combined processes such as water washing, lime neutralization, and calcination. Water washing removes soluble phosphorus, fluoride, and some heavy metals through dissolution, but it consumes a large amount of water (3-5 tons per ton of phosphogypsum) and generates significant amounts of acidic, fluoride-containing, and phosphorus-containing washing wastewater, which can easily cause secondary pollution if not properly treated. Lime neutralization adjusts the pH of the phosphogypsum by adding lime or lime slurry, converting soluble phosphorus and fluoride into insoluble calcium phosphate and calcium fluoride precipitates. However, its effect on solidifying heavy metals is limited, and the long-term environmental stability of the treated product is difficult to guarantee. Calcination decomposes organic matter and some impurities in phosphogypsum at high temperatures of 600-900℃, but it has high energy consumption, poor control of volatile heavy metals such as mercury, complex exhaust gas treatment systems, and high investment and operating costs.

[0005] In recent years, alkali-activated cementitious material technology has received widespread attention in the field of bulk solid waste resource utilization. Studies have shown that solid wastes such as coal gangue, slag powder, and red mud contain active silicon, aluminum, and calcium components, which can form calcium silicate or aluminosilicate cementitious phases under alkaline conditions. These phases can stabilize and solidify harmful components through physical encapsulation, adsorption, ion exchange, and chemical precipitation. However, existing technologies mostly treat a single type of solid waste individually, lacking a systematic approach to the synergistic utilization of phosphogypsum with various bulk solid wastes such as coal gangue, slag, and red mud. Furthermore, the products prepared by existing methods are mostly dense blocks or powders, lacking granular porous materials that combine granular skeleton stability, good air and water permeability, and efficient solidification capabilities for harmful components. This makes it difficult to meet the dual requirements of porous structure and environmental safety for applications such as soil improvement, microbial attachment, or nutrient slow-release carriers.

[0006] Therefore, developing a method for the synergistic utilization of various bulk solid wastes, achieving efficient and harmless treatment of phosphogypsum, and simultaneously constructing a granular mineral carrier material with a macroporous structure is of great practical significance for promoting the large-scale resource utilization of phosphogypsum and reducing the environmental pressure of solid waste stockpiling. Summary of the Invention

[0007] The purpose of this invention is to provide a method for preparing a phosphogypsum-based porous mineral carrier based on bulk solid waste materials, so as to solve the problems mentioned in the background art.

[0008] To achieve the above objectives, the present invention provides the following technical solution:

[0009] A method for preparing phosphogypsum-based porous mineral carriers based on bulk solid waste materials includes the following steps:

[0010] S1. The phosphogypsum and solid waste precursor are dried, crushed and screened to obtain pretreated powder; the pretreated powder is subjected to primary water washing and secondary to tertiary alkali washing, and after solid-liquid separation, purified wet material is obtained; the purified wet material is dried, and the total mass of the dried solid is recorded as the mass of the dry solid.

[0011] S2. Based on the mass of the solid dry material, weigh out 1% to 3% of liquid sodium silicate with a modulus of 2.2 to 2.3, and dilute it with deionized water to 20% to 24% of the mass of the solid dry material to obtain a diluted liquid sodium silicate solution.

[0012] S3. Mix the solid dried in step S1 with calcium stearate to form granulated alkali-activated dry material;

[0013] S4. The liquid sodium silicate dilution obtained in step S2 is used as an alkali activator and sprayed together with the diluted hydrogen peroxide solution into the granulated alkali-activated dry material. After disc granulation, foaming, curing, room temperature drying and sieving, a phosphogypsum-based porous mineral carrier material is obtained.

[0014] Preferably, based on dry weight, phosphogypsum comprises 75-85 parts, solid waste precursor comprises 15-25 parts, and the total solid components comprise 100 parts.

[0015] The solid waste precursors include coal gangue, S95 slag powder, red mud, etc.

[0016] Preferably, the fineness of the pretreated powder is such that the passing rate through a 100-mesh sieve is not less than 95%.

[0017] Preferably, the primary water washing and the secondary to tertiary alkaline washing in step S1 adopt a multi-stage countercurrent washing system. The system includes a primary water washing tank and a secondary to tertiary alkaline washing tank. The water washing uses deionized water with a solid-liquid ratio of 1:20 and is stirred for 10 minutes. The alkaline washing uses lime water with a pH of 11 with a solid-liquid ratio of 1:20 and is stirred for 10 minutes.

[0018] Preferably, the amount of calcium stearate added in step S3 is 0.1% to 0.4% based on the mass of the solid dry material;

[0019] In step S4, the hydrogen peroxide is added in the form of a diluted hydrogen peroxide solution with a mass fraction of 8% to 12%, and the amount of diluted hydrogen peroxide solution added is 20% to 24% of the mass of the solid dry material.

[0020] Preferably, the amount of calcium stearate added in step S3 is 0.2% of the mass of the solid dry material.

[0021] Preferably, the total amount of the liquid sodium silicate diluent and the hydrogen peroxide diluent added is 40% to 48% of the mass of the solid dry material.

[0022] Preferably, in step S4, the granulation disc of the disc granulator has an inclination angle of 45°-50°, a rotation speed of 30-35 rpm, a distance of 2-5 mm between the scraper and the disc surface, and a granulation time of 3-8 min; the target particle size of the obtained wet granules is 1-5 mm.

[0023] Preferably, in step S4, the foaming, curing and maintenance are carried out at room temperature for 3 to 7 days, and the product is dried in the air until the moisture content of the finished product is not higher than 5%.

[0024] Application of phosphogypsum-based porous mineral carrier materials prepared according to any of the above methods as skeleton materials for soil conditioners, soil conditioning agents, microorganisms, or nutrient carriers.

[0025] Compared with the prior art, the beneficial effects of the present invention are:

[0026] (1) This invention uses phosphogypsum as the main raw material and synergistically utilizes various bulk solid wastes such as coal gangue, S95 slag powder, and red mud to leverage the complementary advantages of different solid wastes in terms of chemical composition and physical properties. Phosphogypsum provides a calcium source, while coal gangue, slag powder, and red mud provide active silicon and aluminum components, generating CSH and CASH gels under alkaline activation conditions to form a stable gel skeleton. This achieves large-scale disposal of various solid wastes, avoiding the problems of low utilization rate and poor performance of single solid wastes, and improving the comprehensive utilization level of solid waste resources.

[0027] (2) The method of combining primary water washing with multi-stage alkaline washing effectively removes soluble phosphorus, fluorine and free acid from phosphogypsum. At the same time, during the alkaline-activated gelation reaction, the residual soluble phosphorus and fluorine are converted into insoluble calcium phosphate and calcium fluoride precipitates. Heavy metal ions are solidified in the silicate cement phase and calcium silicate / aluminosilicate cement phase skeleton through multiple mechanisms such as physical encapsulation, adsorption, ion exchange and chemical precipitation.

[0028] (3) Utilizing the property of hydrogen peroxide decomposing and releasing oxygen under alkaline conditions, chemical gas generation and pore-forming technology is introduced into the alkaline-activated gelation system. At the same time, the foam-stabilizing effect of calcium stearate is combined to form a macroporous structure with good connectivity and uniform pore size distribution inside the particles. The disc granulation process makes the material into regular granules, which have good air and water permeability and suitable particle strength, making it convenient for subsequent processing, transportation and use. Attached Figure Description

[0029] Figure 1 This is one of the flowcharts of the present invention. Detailed Implementation

[0030] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0031] Example 1:

[0032] Please see Figure 1 As shown, the method for preparing a phosphogypsum-based porous mineral carrier based on bulk solid waste materials includes the following steps:

[0033] S1. Raw material pretreatment, including:

[0034] Phosphogypsum, with an original pH of 2.5, free water content of 18.6%, calcium sulfate dihydrate content of 82.3%, water-soluble fluoride content of 0.52%, and water-soluble P2O5 content of 0.89%;

[0035] The main chemical components of coal gangue are SiO2 52.3%, Al2O3 18.7%, Fe2O3 6.5%, and CaO 3.2%. The specific surface area of ​​S95 slag powder is 420 m² / kg, and its 28-day activity index is 96%.

[0036] Red mud has the following main chemical components: Fe2O3 32.5%, Al2O3 18.3%, SiO2 14.6%, CaO 13.2%, and pH value 11.8.

[0037] Phosphogypsum, coal gangue, and red mud were placed separately in a forced-air drying oven and dried at 105℃ until the moisture content was below 3%. After drying, the phosphogypsum was coarsely crushed by a jaw crusher and then ground into powder using a ball mill until a 96% pass rate was achieved on a 100-mesh sieve. The coal gangue and red mud were ground separately until a pass rate of over 95% was achieved on a 100-mesh sieve. The S95 slag powder was used directly without further drying and grinding.

[0038] Weigh out the following solid raw materials by dry basis weight: 80 parts phosphogypsum, 14 parts coal gangue, 4 parts S95 slag powder, and 2 parts red mud, totaling 100 parts. Put the above powders into a mixing tank, add deionized water, control the solid-liquid ratio at 1:20, stir and react at room temperature for 10 minutes, perform a first-stage water wash, let it stand and settle after stirring, pour off the supernatant, and pump the lower slurry into an alkaline washing tank.

[0039] Add lime water with pH=11 to the alkaline washing tank, with a solid-liquid ratio of 1:20, stir at room temperature for 10 minutes, allow to settle, and then discard the supernatant. Repeat the above alkaline washing operation once, performing a total of two alkaline washing stages. After alkaline washing, the slurry is separated by plate and frame filter press. The filter cake is rinsed with deionized water until the pH of the rinsing solution is 10.0±0.2, yielding purified wet material.

[0040] S2. Preparation of alkaline activator dilution solution, including:

[0041] Weigh 2% of liquid sodium silicate with a modulus of 2.3 based on the weight of the solid dry material, and dilute it until the final total weight is 20% of the solid dry material weight. Stir well to obtain a diluted liquid sodium silicate solution. Do not add additional sodium hydroxide to adjust the modulus, and seal for later use.

[0042] S3, Granulation and Alkali-Activated Dry Material Preparation, including:

[0043] The above-mentioned purified wet material was placed in a forced-air drying oven and dried at 105℃ until the moisture content was less than 1%. After cooling, it was pulverized and passed through a 100-mesh sieve to obtain purified dry powder. 1000 parts of the purified dry powder were weighed and 2 parts of calcium stearate (accounting for 0.2% of the mass of the solid dry material) were added. The mixture was placed in a three-dimensional mixer and mixed for 15 minutes at a speed of 30 rpm. After uniform mixing, granulated alkali-activated dry material was obtained.

[0044] S4. Disc granulation and foaming curing, including:

[0045] Adjust the tilt angle of the disc granulator to 48°, the rotation speed to 32 rpm, and the distance between the scraper and the disc surface to 3 mm. Take 500 parts of the above-mentioned granulated alkali-activated dry material and place it in the granulation disc;

[0046] Preparation of diluted hydrogen peroxide solution: Take 30% hydrogen peroxide solution, calculate the amount based on 24% of the solid dry material mass, dilute the 30% hydrogen peroxide stock solution with deionized water to 3 times the original volume, stir evenly to obtain diluted hydrogen peroxide solution.

[0047] The liquid sodium silicate dilution obtained in step S2 is premixed with the above-mentioned diluted hydrogen peroxide solution to obtain a mixed foaming alkali activating solution, the total amount of which accounts for 44% of the mass of the solid dry material;

[0048] The mixed foaming alkali activating solution is atomized and evenly sprayed into a rotating granulation disc through a dual-fluid nozzle. Spraying is carried out while rotating, and the granulation time is 7 minutes, so that the material agglomerates into balls to obtain wet granules with a particle size of 1-5 mm.

[0049] The wet granules were removed from the granulation tray, spread evenly on a pallet, and placed in a constant temperature and humidity chamber for 5 days under normal temperature (20-25℃) and relative humidity ≥90%. During the curing period, hydrogen peroxide continuously decomposed under alkaline conditions, releasing oxygen and forming a connected macroporous structure inside the granules. At the same time, liquid sodium silicate provided soluble silicate components, which, under the action of the calcium source provided by phosphogypsum and the silica-alumina mineral surface provided by coal gangue, formed silicate cement phases and calcium-containing silicate / aluminosilicate cement phases, thereby enhancing the bonding between granules and the stability of the framework.

[0050] After curing, the granules are placed in a forced-air drying oven and dried at 85°C until the moisture content is below 5%. After cooling, they are sieved using a standard vibrating sieve to collect 3-5 mm particles, which are the finished phosphogypsum-based porous mineral carrier materials.

[0051] Example 2

[0052] Please see Figure 1 As shown, the method for preparing a phosphogypsum-based porous mineral carrier based on bulk solid waste materials includes the following steps:

[0053] S1. Raw material pretreatment, including:

[0054] Phosphogypsum, with an original pH of 3.1, free water content of 20.2%, calcium sulfate dihydrate content of 79.8%, water-soluble fluoride content of 0.48%, and water-soluble P2O5 content of 0.76%;

[0055] Coal gangue, with main chemical components of 54.1% SiO2, 17.2% Al2O3, 5.8% Fe2O3, and 2.9% CaO; S95 slag powder has a specific surface area of ​​435 m² / kg and a 28-day activity index of 97%; red mud, with main chemical components of 31.2% Fe2O3, 19.1% Al2O3, 15.3% SiO2, and 12.8% CaO, and a pH value of 11.5;

[0056] Phosphogypsum, coal gangue, and red mud were placed separately in a forced-air drying oven and dried at 105℃ until the moisture content was below 3%. After drying, the phosphogypsum was coarsely crushed by a jaw crusher and then ground into powder using a ball mill until a 97% pass rate was achieved on a 100-mesh sieve. The coal gangue and red mud were ground separately until a pass rate of over 95% was achieved on a 100-mesh sieve. The S95 slag powder was used directly without further drying and grinding.

[0057] Weigh out the following solid raw materials by dry basis weight: 75 parts phosphogypsum, 18 parts coal gangue, 5 parts S95 slag powder, and 2 parts red mud, totaling 100 parts. Put the above powders into a mixing tank, add deionized water, control the solid-liquid ratio at 1:20, stir and react at room temperature for 10 minutes, perform a first-stage water wash, let it stand and settle after stirring, pour off the supernatant, and pump the lower layer slurry into an alkaline washing tank.

[0058] Add lime water with pH=11 to the alkaline washing tank at a solid-liquid ratio of 1:20, stir at room temperature for 10 minutes, allow to settle, and then discard the supernatant. Repeat the above alkaline washing operation twice, for a total of three stages of alkaline washing. After alkaline washing, the slurry is separated by plate and frame filter press. The filter cake is rinsed with deionized water until the pH of the rinsing solution is 10.0±0.2, yielding purified wet material.

[0059] S2. Preparation of alkaline activator dilution solution, including:

[0060] Weigh 1% of liquid sodium silicate with a modulus of 2.2 based on the weight of the solid dry material, dilute it with deionized water to 24% of the solid dry material weight, stir well, and obtain a diluted liquid sodium silicate solution. Do not add additional sodium hydroxide to adjust the modulus, and seal for later use.

[0061] S3, Granulation and Alkali-Activated Dry Material Preparation, including:

[0062] The above-mentioned purified wet material was placed in a forced-air drying oven and dried at 105℃ until the moisture content was less than 1%. After cooling, it was pulverized and passed through a 100-mesh sieve to obtain purified dry powder. 1000 parts of purified dry powder were weighed, 3 parts of calcium stearate were added, and the mixture was placed in a three-dimensional mixer and mixed for 15 minutes at a speed of 30 rpm. After uniform mixing, granulated alkali-activated dry material was obtained.

[0063] S4. Disc granulation and foaming curing, including:

[0064] Adjust the tilt angle of the disc granulator to 45°, the rotation speed to 30 rpm, and the distance between the scraper and the disc surface to 4 mm. Take 500 parts of the above-mentioned granulated alkali-activated dry material and place it in the granulation disc;

[0065] Preparation of diluted hydrogen peroxide solution: Take 8% hydrogen peroxide solution by mass, calculate the amount based on 20% of the mass of the solid dry material, stir evenly to obtain diluted hydrogen peroxide solution;

[0066] The liquid sodium silicate dilution obtained in step S2 is premixed with the above-mentioned diluted hydrogen peroxide solution to obtain a mixed foaming alkali activating solution, the total amount of which accounts for 44% of the mass of the solid dry material;

[0067] The mixed foaming alkali activating solution is atomized and evenly sprayed into a rotating granulation disc through a dual-fluid nozzle. Spraying is carried out while rotating, and the granulation time is 5 minutes, so that the material agglomerates into balls to obtain wet granules with a particle size of 1-5 mm.

[0068] The wet granules were removed from the granulation tray, spread evenly on a pallet, and placed in a constant temperature and humidity chamber for curing at room temperature (20–25°C) and relative humidity ≥90% for 3 days. During curing, hydrogen peroxide continuously decomposed under alkaline conditions, releasing oxygen and forming a connected macroporous structure inside the granules. Simultaneously, liquid sodium silicate provided soluble silicate components, which, under the action of the calcium source provided by phosphogypsum and the silica-alumina mineral surface provided by coal gangue, formed silicate cement phases and calcium-containing silicate / aluminosilicate cement phases, thereby enhancing the intergranular bonding and framework stability.

[0069] After curing, the granules are placed in a forced-air drying oven and dried at 60°C until the moisture content is no more than 5%. After cooling, they are sieved using a standard vibrating sieve to collect 3-5 mm particles, which are the finished phosphogypsum-based porous mineral carrier materials.

[0070] Experimental example:

[0071] To verify the beneficial effects of the phosphogypsum-based porous mineral carrier material described in this invention, the following three sample groups were set up for comparative testing:

[0072] Control group (raw phosphogypsum): Raw phosphogypsum without any treatment.

[0073] Experimental Group 1 (Water Washing and Alkali Washing Treatment Group): Phosphogypsum and auxiliary solid waste materials were mixed in the same proportion as in the experimental group, and only primary water washing and secondary alkali washing treatment were performed.

[0074] Experimental Group 2 (Porous Mineral Carrier Preparation Group): The test method for the phosphogypsum-based porous mineral carrier material prepared according to the method described in Example 1 of this invention after water washing and alkali washing of phosphogypsum and auxiliary solid waste materials includes:

[0075] The testing methods include:

[0076] Adhered water content: Take about 50g of each sample and dry it in a forced-air drying oven at 40℃±2℃ until constant weight, and calculate the percentage of weight loss.

[0077] The content of calcium sulfate dihydrate was determined by EDTA titration, using calcein as an indicator, and the mass fraction of calcium sulfate was calculated.

[0078] Water-soluble fluoride content: Weigh 10.0g of the sample that has passed through a 2mm sieve, add 100mL of deionized water, shake and extract for 30 minutes, filter, and then determine the fluoride ion concentration in the filtrate using the ion-selective electrode method (GB / T 7484-87).

[0079] Water-soluble P2O5 content: The water extract of the sample was prepared according to the above method, and the absorbance was measured at a wavelength of 700 nm using the phosphomolybdic blue spectrophotometric method (HJ 593-2010).

[0080] pH value: Weigh 10.0g of sample that has passed through a 2mm sieve, add 100mL of deionized water to which carbon dioxide has been removed, stir for 2 minutes and let stand for 30 minutes, then measure the supernatant with a pH meter.

[0081] pH test: Weigh 2.0 g of sample that has passed through a 2 mm sieve, add 40 mL of deionized water (solid-liquid ratio 1:20), shake on a shaker for 10 minutes, then centrifuge at 3000 rpm for 10 minutes. Take the supernatant and measure the pH value using a pH meter. Perform three parallel tests for each sample and take the average value.

[0082] Water absorption rate: The determination of water absorption rate was carried out in accordance with the water absorption rate determination section of GB / T 1966-1996 "Determination of Apparent Porosity and Water Absorption Rate of Porous Ceramics". Weigh the mass of the dried sample, boil it in boiling water for 2 hours, remove it, cool it, weigh the saturated water-absorbed mass, and calculate the water absorption rate.

[0083] Soil bulk density: The method was performed according to the ring sampler method in NY / T 1121.4-2006 "Soil Testing Part 4: Determination of Soil Bulk Density". The sample was dried at 105℃ to constant weight, placed in a ring sampler of known volume (V=100 cm³), weighed, and the dry mass per unit volume was calculated in g / cm³.

[0084] Percentage of water-stable aggregates (>0.25 mm): Refer to the wet sieving method in NY / T 1121.19-2008 "Soil Testing Part 19: Determination of Water-Stable Aggregates in Soil". Weigh 50.0 g of air-dried sample, place it on a 0.25 mm sieve, and wet sieve it in distilled water at an oscillation frequency of 30 times / minute for 5 minutes. Dry the residue on the sieve at 105℃ and weigh it. Calculate the percentage of the total mass of water-stable aggregates >0.25 mm.

[0085] The immediate extraction pH of wet granules was determined by different amounts of liquid sodium silicate. Samples were prepared according to the method in Example 1, using 1%, 2%, and 3% of the solid dry material mass of liquid sodium silicate stock solution (modulus 2.3, solid content 40%). The immediate extraction pH of the wet granules was measured immediately after granulation. Measurement method: 2.0 g of sample was weighed, and deionized water was added at a solid-liquid ratio of 1:20. The mixture was shaken for 10 min, centrifuged for 10 min, and the pH of the supernatant was measured.

[0086] The test results are shown in the table below:

[0087] Table 1. Basic physicochemical properties of different treatment groups

[0088] Testing items control group Experimental group 1 Experimental group 2 Adhered water (%) 18.6 1.2 0.8 Calcium sulfate dihydrate (%) 82.3 85.2 86.5 Water-soluble fluoride (%) 0.52 0.09 0.05 <![CDATA[Water-soluble P2O5 (%)]]> 0.89 0.18 0.12 pH value 2.5 8.8 9.2

[0089] Table 2. Total Heavy Metal Data of Phosphogypsum-Based Porous Mineral Carriers (with Coal Gangue as Auxiliary Solid Waste, Ratio 5:1)

[0090] PG+ Coal Gangue CG 254.3 633.7 2.9 27.3 44.3 25.7

[0091] Table 3. pH data of water leaching of phosphogypsum-based porous mineral carriers (with coal gangue as auxiliary solid waste, ratio 5:1).

[0092] PG+ Coal Gangue CG 4.29 4.23 4.22

[0093] Table 4 Comparison of physical properties of different samples

[0094] Testing items Control group (original phosphogypsum) Experimental Group 1 (Water Washing and Alkali Washing Treatment Group) Experimental Group 2 (Porous Ore Support Preparation Group) Water absorption rate (%) 35.2 28.6 48.6 Soil bulk density (g / cm³) 1.28 1.35 0.68 Percentage of water-stable aggregates (>0.25 mm, %) 12.5 18.3 57.56

[0095] Table 5 pH of wet particle extraction under different amounts of liquid sodium silicate

[0096] Dosage of liquid sodium silicate stock solution (%) pH parallel values Average pH 1% 7.14、7.19、7.17 7.17 2% 8.76、8.78、8.78 8.77 3% 9.30、9.19、9.23 9.24

[0097] In summary, compared with untreated raw phosphogypsum and samples treated only by water washing and alkali washing, the phosphogypsum-based porous mineral carrier material prepared by this invention further reduces the content of harmful components such as water-soluble fluorine and water-soluble P2O5, and increases the pH value to near neutral to weakly alkaline, significantly improving environmental safety. At the same time, its water absorption rate is increased, soil bulk density is reduced, and the proportion of water-stable aggregates is high, indicating that the material has excellent pore structure, good air and water permeability, and aggregate stability, which can meet the dual requirements of porous structure and environmental safety for applications such as soil improvement, microbial attachment, and nutrient slow-release carriers.

[0098] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a phosphogypsum-based porous mineral carrier based on bulk solid waste materials, characterized in that, Includes the following steps: S1. Dry, crush and screen the phosphogypsum and solid waste precursor respectively to obtain pretreated powder; The pretreated powder is subjected to a first-stage water washing and a second- to third-stage alkaline washing. After solid-liquid separation, purified wet material is obtained. The purified wet material is dried, and the total mass of the dried solid is recorded as the mass of the dry solid. S2. Based on the mass of the solid dry material, weigh out 1% to 3% of liquid sodium silicate with a modulus of 2.2 to 2.3, and dilute it with deionized water to 20% to 24% of the mass of the solid dry material to obtain a diluted liquid sodium silicate solution. S3. Mix the solid dried in step S1 with calcium stearate to form granulated alkali-activated dry material; S4. The liquid sodium silicate dilution obtained in step S2 is used as an alkali activator and sprayed together with the diluted hydrogen peroxide solution into the granulated alkali-activated dry material. After disc granulation, foaming, curing, room temperature drying and sieving, a phosphogypsum-based porous mineral carrier material is obtained.

2. The method for preparing phosphogypsum-based porous mineral carriers based on bulk solid waste materials according to claim 1, characterized in that: On a dry basis, the phosphogypsum is 75-85 parts, the solid waste precursor is 15-25 parts, and the total of all solid components is 100 parts.

3. The method for preparing phosphogypsum-based porous mineral carriers based on bulk solid waste materials according to claim 1, characterized in that: The fineness of the pretreated powder is such that the passing rate through a 100-mesh sieve is not less than 95%.

4. The method for preparing phosphogypsum-based porous mineral carriers based on bulk solid waste materials according to claim 1, characterized in that: The primary water washing and the secondary to tertiary alkaline washing in step S1 adopt a multi-stage countercurrent washing system. The system includes a primary water washing tank and a secondary to tertiary alkaline washing tank. The water washing uses deionized water with a solid-liquid ratio of 1:20 and is stirred for 10 minutes. The alkaline washing uses lime water with a pH of 11 with a solid-liquid ratio of 1:20 and is stirred for 10 minutes.

5. The method for preparing phosphogypsum-based porous mineral carriers based on bulk solid waste materials according to claim 1, characterized in that: In step S3, the amount of calcium stearate added is 0.1% to 0.4% based on the mass of the solid dry material. In step S4, the hydrogen peroxide is added in the form of a diluted hydrogen peroxide solution with a mass fraction of 8% to 12%, and the amount of diluted hydrogen peroxide solution added is 20% to 24% of the mass of the solid dry material.

6. The method for preparing phosphogypsum-based porous mineral carriers based on bulk solid waste materials according to claim 1, characterized in that: In step S3, the amount of calcium stearate added is 0.2% of the mass of the solid dry material.

7. The method for preparing phosphogypsum-based porous mineral carriers based on bulk solid waste materials according to claim 1, characterized in that: The total amount of the liquid sodium silicate diluent and the hydrogen peroxide diluent added is 40% to 48% of the mass of the solid dry material.

8. The method for preparing phosphogypsum-based porous mineral carriers based on bulk solid waste materials according to claim 1, characterized in that: In step S4, the granulation disc of the disc granulator has an inclination angle of 45°-50°, a rotation speed of 30-35 rpm, a distance of 2-5 mm between the scraper and the disc surface, and a granulation time of 3-8 min; the target particle size of the obtained wet granules is 1-5 mm.

9. The method for preparing phosphogypsum-based porous mineral carriers based on bulk solid waste materials according to claim 1, characterized in that: In step S4, the foaming, curing and maintenance are carried out at room temperature for 3 to 7 days, and then dried in the air until the moisture content of the finished product is no higher than 5%.

10. The application of the phosphogypsum-based porous mineral carrier material prepared according to any one of claims 1-9 as a skeleton material for soil conditioner, soil conditioning agent, microorganism or nutrient carrier.